tìm gtln của biểu thức : a, A=x/ x^2+2 ; B=x^2/ (x^2+2)^3 giup em voi em dang can rat gap 09/11/2021 Bởi Athena tìm gtln của biểu thức : a, A=x/ x^2+2 ; B=x^2/ (x^2+2)^3 giup em voi em dang can rat gap
Đáp án: Giải thích các bước giải: a) $ A = \dfrac{x}{x² + 2} = \dfrac{1}{2\sqrt{2}} – (\dfrac{1}{2\sqrt{2}}- \dfrac{x}{x² + 2})$ $ = \dfrac{1}{2\sqrt{2}} – \dfrac{x² – 2\sqrt{2}x + 2}{x² + 2}$ $ = \dfrac{1}{2\sqrt{2}} – \dfrac{(x – \sqrt{2})²}{x² + 2} ≤ \dfrac{1}{2\sqrt{2}} $ $ ⇒ GTLN$ của $A = \dfrac{1}{2\sqrt{2}} ⇔ x – \sqrt{2} = 0 ⇔ x = \sqrt{2}$ b) $ B = \dfrac{x²}{(x² + 2)³} = \dfrac{1}{27} – (\dfrac{1}{27} – \dfrac{x²}{(x² + 2)³})$ $ = \dfrac{1}{27} – \dfrac{(x² + 2)³ – 27x²}{27(x² + 2)³}$ $ = \dfrac{1}{27} – \dfrac{x^{6} + 6x^{4} – 15x² + 8}{27(x² + 2)³}$ $ = \dfrac{1}{27} – \dfrac{(x² – 1)²(x² + 8)}{27(x² + 2)³} ≤ \dfrac{1}{27} $ $ ⇒ GTLN$ của $B = \dfrac{1}{27} ⇔ x² – 1 = 0 ⇔ x = ± 1$ Bình luận
Đáp án:
Giải thích các bước giải:
a) $ A = \dfrac{x}{x² + 2} = \dfrac{1}{2\sqrt{2}} – (\dfrac{1}{2\sqrt{2}}- \dfrac{x}{x² + 2})$
$ = \dfrac{1}{2\sqrt{2}} – \dfrac{x² – 2\sqrt{2}x + 2}{x² + 2}$
$ = \dfrac{1}{2\sqrt{2}} – \dfrac{(x – \sqrt{2})²}{x² + 2} ≤ \dfrac{1}{2\sqrt{2}} $
$ ⇒ GTLN$ của $A = \dfrac{1}{2\sqrt{2}} ⇔ x – \sqrt{2} = 0 ⇔ x = \sqrt{2}$
b) $ B = \dfrac{x²}{(x² + 2)³} = \dfrac{1}{27} – (\dfrac{1}{27} – \dfrac{x²}{(x² + 2)³})$
$ = \dfrac{1}{27} – \dfrac{(x² + 2)³ – 27x²}{27(x² + 2)³}$
$ = \dfrac{1}{27} – \dfrac{x^{6} + 6x^{4} – 15x² + 8}{27(x² + 2)³}$
$ = \dfrac{1}{27} – \dfrac{(x² – 1)²(x² + 8)}{27(x² + 2)³} ≤ \dfrac{1}{27} $
$ ⇒ GTLN$ của $B = \dfrac{1}{27} ⇔ x² – 1 = 0 ⇔ x = ± 1$